2020
DOI: 10.1088/1361-665x/ab8749
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-variable frequency pendulum isolator with high-performance materials

Abstract: The spherical surface of the friction pendulum system (FPS) inevitably introduce a constant dominant period, which may lead to resonance problem when subjected to the ground motions with long-period components. In this study, a multiple-variable frequency pendulum isolator (MVFPI) was developed to overcome this limitation. The sliding surface of the MVFPI was predefined as a continuous piecewise function to combine the seismic performance of MVFPI with different seismic intensities. The high-performance materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In view of the effectiveness of incorporating the SMA with different isolators for response mitigation [14,[42][43][44][45][46][47][48][49][50][51][52], the advantages of the SMA, i.e., superelastic re-centering and energy dissipation, show the promising prospect of application in structural seismic resilience enhancement [33,43]. Particularly, several superelastic seismic isolators, e.g., superelastic flat sliding bearing [47][48][49][50][51][52] and superelastic friction pendulum [14,[53][54][55][56][57], in which the friction-based isolators are incorporated with the SMA wires/ cables, have been investigated and seismic performances have been analytically and experimentally demonstrated. e SMA utilized in the superelastic friction pendulum is to enhance the re-centering capacity [14,53].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the effectiveness of incorporating the SMA with different isolators for response mitigation [14,[42][43][44][45][46][47][48][49][50][51][52], the advantages of the SMA, i.e., superelastic re-centering and energy dissipation, show the promising prospect of application in structural seismic resilience enhancement [33,43]. Particularly, several superelastic seismic isolators, e.g., superelastic flat sliding bearing [47][48][49][50][51][52] and superelastic friction pendulum [14,[53][54][55][56][57], in which the friction-based isolators are incorporated with the SMA wires/ cables, have been investigated and seismic performances have been analytically and experimentally demonstrated. e SMA utilized in the superelastic friction pendulum is to enhance the re-centering capacity [14,53].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Several studies have revealed that combining the SMA device with isolators is particularly efficient for residual displacement mitigation. [33][34][35][36][37][38][39] Particularly, considering the advantages of the SMA as damping and re-centering components, several SMA-based isolators, which combine the superelastic SMA wire/cables with the traditional friction isolators, have been examined for performance improvement of structures, for example, the SMA-based pure-friction sliding bearing, [38][39][40][41][42][43][44] SMA-friction pendulum bearing, [45][46][47][48][49] which demonstrated the feasibility using the SMA device to enhance the structural seismic resilience. Note that when the pure-friction sliding bearing integrates with SMA, the lateral stiffness and re-centering capability are all dependent on the SMA device, [38][39][40] which means that the SMA device needs to be fabricated using much more amount of SMA wires than the SMA-friction pendulum bearing.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its variable sliding surface, the VFPI system can shift the natural frequency of the isolation system away from predominant frequency of long-period ground motions. Han et al (2020) investigated potential of combining a VFPI system with SMA wires to reduce fabrication complexity of VFPI systems and further control isolation displacements. In addition, Cao et al (2020) proposed a multi-level SMA/lead rubber bearing (LRB) isolation system to reduce isolator displacement without sacrificing isolation efficiency and increasing the force demand of substructure.…”
Section: Introductionmentioning
confidence: 99%